Assessment of safety of performing percutaneous coronary intervention after a recent episode of gastrointestinal bleeding. (2nd January 2016) - Karim, Saima; Ador-Dionisio, Sweetheart T.; Karim, Munira; Karim, Mohammad; Khan, Sadaf S.; Atreja, Ashish; Ellis, Stephen
Abstract : Background: Little literature exists on the risk of performing coronary intervention (PCI) on patients who have had recent gastrointestinal bleeding (GIB), although bleeding after PCI has been identified as a risk factor for long-term mortality.Methods: Patients within the Cleveland Clinic PCI database who had acute GIB within 30 days preceding PCI during the same hospitalization ( n = 79) were retrospectively compared to those who had PCI without recent GIB ( n = 10 979) for mortality and need for revascularization. Baseline characteristics, laboratory values, procedures, morbidities, and mortality were compared using chi-square test for categorical variables and using Wilcoxon rank sum test for continuous variables. Mortality data was obtained using Social Security Death Index and demonstrated using Kaplan–Meier method.Results: The GIB group had more prevalent history of peptic ulcer disease, GIB, gastrointestinal or liver disease ( P < 0.0001), transient ischemic accident ( P = 0.017), peripheral vascular disease ( P = 0.0002), significant carotid artery occlusion ( P = 0.023), and myocardial infarction ( P < 0.0001). 47% of patients had upper GIB with 20% needing endoscopic intervention. This group had more anemia ( P < 0.0001), heart failure ( P = 0.0001), cardiogenic shock (10% versus 1.4%, P < 0.001), cardiac arrest (7.6% versus 1%, P < 0.001). GIB group had worse in-hospital mortality ( P < 0.0001), long-term mortality ( P < 0.001), and a 7.6% re-bleeding incidence.Conclusions: Overall, the patients who had GIB preceding PCI had higher in-hospital mortality and long-term mortality compared with those without GIB before PCI.